Novel ALD-assisted growth of ZnO nanorods on graphene and its Cu2ZnSn(SxSe1−x)4 solar cell application. Issue 6 (15th January 2015) - Jiao, Kejia; Wu, Xiaofeng; Duan, ChunYang; Zhang, Dangwen; Wang, Yu; Chen, Yunfa
Abstract : A novel ALD-assisted growth of ZnO nanorods (NRs) on graphene is reported. The key step is the nondestructive deposition of a uniform ALD–ZnO seed layer on graphene. After obtaining graphene/ZnO(NRs) structure, its applications in CZTSSe solar cells are demonstrated. Abstract : The hydrothermal growth of ZnO nanorods on graphene draws a specific interest for the advantages of low-temperature processability over a large area and low cost, but challenges still remain in directly growing uniform ZnO seed layers on pristine graphene without impairing its beneficial properties. In this work, the direct growth of ZnO seed layers on graphene via H2 O-based atomic layer deposition (ALD) has been investigated. It is found that uniform ZnO thin films can be deposited on graphene via ALD using a combination of single-layer graphene/Cu stacks as substrates and a facile pre-H2 O treatment process. After growing ZnO nanorods on graphene, its photovoltaic application in a Cu2 ZnSn(S x Se1− x )4 (CZTSSe) solar cell is demonstrated. The performance of graphene-based cells approaches that of ITO-based cells with similar architectures, highlighting that graphene is a potential replacement for ITO in optoelectronic devices. The method reported herein for fabricating ZnO nanorods on graphene using ALD–ZnO as seed layers preserves its properties, and is thus applicable to a wide variety of graphene-based nanoelectronic devices.